Developing Writing Skills for Professional Purposes - Nesamalar Chitravelu (Journal of Modern Languages)
This paper is an attempt to reiterate some of the broad policy decisions that are mentioned in Roe's article (1994) Bnd to elaborate some of their corollaries for the professional strand of the Project. The paper also attempts to provide the perspectives necessary to see how the Project relates to national aspirations and needs since a central thesis of this research enterprise is that 'language is an instrument of social process’, that it is a tool for getting things done and that any meaningful yardstick devised for evaluating language outcomes must necessarily include the context within which the language tasks are to be performed.